2016
DOI: 10.1016/j.egja.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of hemodynamic response to laryngoscopy and endotracheal intubation with two different doses of labetalol in hypertensive patients

Abstract: The present study compared the efficacy of two different doses of labetalol, for attenuation of hemodynamic response to laryngoscopy and intubation in hypertensive patients. Patients and methods: 75 hypertensive patients, aged 18-60 years undergoing elective surgical procedures, require general anesthesia and orotracheal intubation. Patients were allocated to any of the three groups (25 each), Group C (control) 5 ml 0.9% saline. Group L1 (labetalol) 0.15 mg/kg diluted with 0.9% saline to 5 ml. Group L2 (labeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…It is, therefore, of prime importance to prevent the likely hemodynamic changes following tracheal intubation in hypertensive patients. 15 Attenuation of hemodynamic stress response to L&I in normotensive patients has been documented in various studies in the literature. A study by Serhat Koc et al compared 400 mg and 800 mg of gabapentin, and they reported that the lower dose was ineffective in preventing pressor response after tracheal intubation.…”
Section: Discussionmentioning
confidence: 98%
“…It is, therefore, of prime importance to prevent the likely hemodynamic changes following tracheal intubation in hypertensive patients. 15 Attenuation of hemodynamic stress response to L&I in normotensive patients has been documented in various studies in the literature. A study by Serhat Koc et al compared 400 mg and 800 mg of gabapentin, and they reported that the lower dose was ineffective in preventing pressor response after tracheal intubation.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Labetalol is a moderately lipid soluble drug with the peak effect on Intravenous administration is 5 -15 minutes. 11 In the study conducted by Kumar R et al 12 between 0.15mg/kg and 0.3mg/kg doses of Labetalol on suppression of pressor responses to laryngoscopy and endotracheal intubation, the authors found out that both the doses of Labetalol were efficient in supressing the haemodynamic stress response to laryngoscopy and intubation in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It can also lead to cerebrovascular accidents in hypertensive patients with cerebrovascular disease. 12 Various drug including β-blockers such as Labetalol, 13 and Esmolol, 14 Opioids, Lidocaine, 15,16 Nitroglycerine, alpha adrenergic agonists such as Clonidine, 17 and dexmedetomidine, 17 calcium channel blockers such as Diltiazem, 18 and have been used for obtunding the stress response. Lidocaine, whether given intravenously or through an endotracheal tube, successfully prevents the rise in blood pressure but fails to prevent the rise in heart rate.…”
Section: Discussionmentioning
confidence: 99%